IMPORTANT TREE STRUCTURE CONCEPTS: binary and balanced binary (AVL) - Colombo, Diogo Augusto; Oliani Junior, Santo (Revista Interface Tecnológica, 2023)
Currently, the labor market in the area of ​​development demands qualified and specialized labor. Future developers should highlight the data structure methods, and, among them, one of the most important and that most makes those who know how to use it stand out is the tree structure, which includes the structure of binary and binary trees balanced (AVL). Thus, this article aims to highlight, analyze, explain and describe how the processes of using these structures are, based on the methodology of bibliographical research through books, magazines and articles, in order to highlight the differences between binary trees and AVL and demonstrate their similar factors. Finally, it is concluded that it is of paramount importance for a programmer to know and know how to implement.
Keywords: Trees; Binary Trees; AVL Trees; Developers; Data Dtructure